ANALYSIS OF TRANSLATION TECHNIQUES OF 'UCHIAGE HANABI' SONG AND COVERSONG BY ANDI ADINATA - Sean Annisa Rakanti; Raden Novitasari (Universitas WIdyatama, 2022)
The aims of this research is to describe the single translation technique and the multiple translation technique applied to the lyrics of the song 'Uchiage Hanabi' covered by Andi Adinata's song into Indonesian. In this research, the data are taken from video of Andi Adinata. The theories of translation technique used is the theory of Molina and Albir . The method used a descriptive qualitative method which consists of three stages, namely, the data collection stage, the data analysis and the presentation of the data analysis results. The data collection methods and techniques used are the listening method and the note-taking technique. Data analysis methods and techniques used are intralingua matching methods and determining element sorting techniques. The method used in presenting the results of data analysis is an informal presentation method. The results of this study indicate that there are 5 types of single translation techniques, namely 1 data literal translation technique, 2 data of modulation translation techniques, word to word is 5 data translation techniques, common equivalent translation techniques 2 data and 2 data amplification translation techniques, and the types of multiple translation techniques, namely amplification translation techniques with 4 data literals, amplification translation techniques with 1 data modulation, modulation translation techniques with 3 literals data and modulation translation techniques with the usual equivalent 2 data.